PEMBUATAN KERTAS INDIKATOR ASAM-BASA DARI KULIT BUAH PISANG DAN NAGA - Elda Pelita; Imran Nazar (Politeknik ATI Padang, 2018)
This research about “Acid-Base Indicator Manufacturing from Banana’s and Dragon fruit’s Peel” had done. The research aims to make acid-base indicator from banana’s and dragon fruit’s peel in paper state as chemistry’s learning media. This research was conducted in Polytechnic ATI Padang with banana’s and dragon fruit’s peel as the sample. Descriptive with qualitative approaching was the style of this research. It had two phases which was manufacturing and testing of paper indicator. Data was collected by acid-base indicator from fruit’s peel’s paper test observation. Data analysis in 30 days showed acid-base indicator from banana’s and dragon fruit’s peel’s paper could expressed a different colour in acid, base, and neutral solution. These researches have conclusion that acid-base indicator from banana’s and dragon fruit’s peel’s paper in 30 days interval could be used as acid-base indicator and learning media.